Análise molecular de um novo isolado de geminivírus em tomateiro e sua gama de hospedeiros - Julião, Juliana Alves São (2000)
The geminiviruses are a large and diverse family of plant viruses that infect a broad variety of plants, which are whitefly or leafhopper transmitted. They are characterized by twin icosaedral capsids and one (A) or two (A and B) circular single-stranded DNA genomes. The Geminiviridae family fali into three subgroups (I, II and III) based on the genome organization, host range and type of insect vector. At the moment, the geminiviruses have become one of the most important limiting factors of the tomato production. New geminiviruses have been detected in Minas Gerais State, and one of these viruses is the target of this investigation. Molecular analyses were accomplished through the use of degenerate primers for PCR amplification. Slot-blots with serial dilutions of virus DNA amplicons was used to demonstrate differences in virus concentration in five tomato cultivars, and LIS-SSCP (low ionic strength - single stranded conformational polymorphism) was used to detect differences among virus isolates in a broad host range. The two virus genomes, A and B, were amplified, confirming that this fitovirus is a geminivirus that belongs to the subgroup III, which can infect dicotiledoneous plants. All analyzed samples presented geminivirus symptoms similar to those described for the TRMV (Tomato Rugose Mosaic Virus). Subsequently, diagnosis through PCR was accomplished for 10 different plant species ( squash, eggplant, cabbage, bean, cassava, cucumber, pepper, weed, greenbeans) with the objective of verifying the host range of this new virus. All samples were positive for virus infection since DNA amplicons were detected in all samples. These samples were also submitted to LIS-SSCP-PCR to demonstrate the presence of other virus isolates and to compare virus from different samples. Only pepper samples showed a different SSCP band pattern in comparison to the other hosts. The reason for this may be that the collection of these samples were done in another place, where infected tomato plants were also observed with similar symptoms. In the same experimental field of all hosts, five tomato cultivars with five samples each were randomly selected and virus concentration was investigated though slot-blot. All samples were infected with this new geminivirus; however, there was no significant differences for viral concentration among samples, suggesting that all plants were susceptibles, but with different tolerance leveis, probably associated to stress tolerance. Additionally, to demonstrate that this isolate was a new virus, a restriction mapping of the A genome amplicon was done. Of the 14 enzymes tested, only three recognized specific sequence sites, Hha I, Mbo I and Sal I. Comparisons with the sequences obtained from TGMV, BGMV, PYMV, ToMoV and TRMV indicated that this geminivirus is different.